If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -8 = 2(x + 2) Reorder the terms: -8 + 3x = 2(x + 2) Reorder the terms: -8 + 3x = 2(2 + x) -8 + 3x = (2 * 2 + x * 2) -8 + 3x = (4 + 2x) Solving -8 + 3x = 4 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -8 + 3x + -2x = 4 + 2x + -2x Combine like terms: 3x + -2x = 1x -8 + 1x = 4 + 2x + -2x Combine like terms: 2x + -2x = 0 -8 + 1x = 4 + 0 -8 + 1x = 4 Add '8' to each side of the equation. -8 + 8 + 1x = 4 + 8 Combine like terms: -8 + 8 = 0 0 + 1x = 4 + 8 1x = 4 + 8 Combine like terms: 4 + 8 = 12 1x = 12 Divide each side by '1'. x = 12 Simplifying x = 12
| 5x+62+37+3x+47=180 | | 2+6=9+3 | | y=(12x+60) | | 1/4Y-2/4Y | | -8v-34=7(v-7) | | 8(u+8)=3u+14 | | 7x^2-6x=-1 | | (5x+62)(3x+47)37=180 | | 4=x-7x-8 | | 7(c-7)=6(3+c) | | 1/3(18-6x)=8-3x | | 1/3(18x-6x)=8-3x | | 2=9+w | | -2y+180=x | | 144a^2+b^2-24ab=0 | | 14+2=-2(6y-8) | | -y-3=-9 | | 3(2x+9)=-37+46 | | 3[6+(-2)]= | | b-81b^3=0 | | T(2)-10t=39 | | 2t^4-3= | | 6x-7=5(x-1)+(x-2) | | x^2+6x+9-64=0 | | X(-2)-8=0 | | -x+3+2z=0 | | X-2-8=0 | | 1/4Y-1/2Y=1/6 | | 6x-7=5(x-1)+(x+2) | | 2x^2-4x-4=2 | | (9w-2)(7w-3)=0 | | 8x-28+3x+4=108 |